Pathogens causing urinary tract infections in infants: a european overview by the ESCAPE study group - Alberici, Irene; Wühl, Elke; Mehls, Otto; Schaefer, Franz (European journal of pediatrics, 2015)
Knowledge of the distribution spectrum of causative organisms and their resistance patterns has become a core requirement for the rational and effective management of urinary tract infections. In the context of a prospective trial on the use of antibiotic prophylaxis in infants with underling kidney malformations, we conducted an online survey among paediatric nephrologists on positive urine cultures (July 2010-June 2012) from both hospitalized and non-hospitalized infants under 24 months of age. We collected 4745 urine cultures (UCs) at 18 units in 10 European countries. Escherichia coli was the most frequent bacterium isolated from UCs; however, in 10/16 hospitals and in 6/15 community settings, E. coli was isolated in less than 50 % of the total positive UCs. Other bacterial strains were Klebsiella, Enterococcus, Proteus and Pseudomonas not only from hospital settings. E. coli showed a high resistance to amoxicillin and trimethoprim and variable to cephalosporin. Nitrofurantoin had a good rate of efficacy, with 11/16 hospitals and 11/14 community settings reporting a resistance lower than 5 %.Conclusion: E. coli is the most common organism causing UTIs in infants; however, other bacterial strains are frequently isolated. As a result, antibiotic prophylaxis should be more elastic and adaptable over time in order to guarantee maximum efficacy.